FROM SHAKING TO SHINING: REDUCING STUDENTS’ LANGUAGE ANXIETY THROUGH OUTCOME THINKING PROTOCOL - Sison-Kuiper, Myrna B. (PEOPLE: International Journal of Social Sciences, 2016)
A significant approach that contributes to the reduction of language anxiety (MacIntyre and Gregersen , 2012) and (Dewaele,2013 ) is the Outcome Thinking Protocol ( Kuiper, 2004). Outcome Thinking is a pictorial way of turning off stress and anxiety, replacing complaining and non-acceptance of negative or stressful situations with acceptance. Using a case study design, the paper presented the collective experiences of 15 students who exhibited high anxiety at the onset of their two language classes and then underwent an Outcome Thinking Protocol Workshop for four times, twice a semester. Student participants’ performances in the language classes during the 10-month duration were observed and recorded. With the acceptance protocol approach employed by the teacher, the students were taught to “turn off” their anxiety and replace it with curiosity towards language learning, a real sign of acceptance. Narratives and interviews with observations served as the main tools for data gathering. From the extended texts of the interviews, themes were extracted from the students’ experiences. Triangulation of data was also employed showing the significant improvement of 25%- 30% on the participants’ language learning outcomes. Also, results showed that the reduction of the participants’ language anxiety led to a remarkable improvement in all of their final classroom performance across disciplines, and in their off-campus lives.